Anti-tumor activity of murine peritoneal macrophages induced by porcine skin gelatin - Koide, T.; Kojima, T.; Inamura, Y.; Nagata, H.; Hashimoto, Y.; Sugita, Y.; Maeda, H. (Experimental Oncology, 2008)
Aim: To study the induction of anti-tumor activity of murine peritoneal macrophages in vitro by porcine skin gelatin. Methods: Anti-tumor activity of the macrophages was evaluated with tritium thymidine uptake by target tumor cells. ELISA was used to measure amounts of cytokines secreted in culture medium. Results: The ability of the gelatin to induce anti-tumor activity of the macrophages was stronger than that of lipopolysaccharide of E. coli. Combination of the lipopolysaccharide and interferon-g synergistically stimulated the macrophages but that of the gelatin and interferon-g additionally did. The culture supernatant of the macrophages incubated with the gelatin also showed higher anti-tumor activity than that with the lipopolysaccharide though the lipopolysaccharide was more excellent than the gelatin in stimulating secretion of anti-tumor cytokines (IL-1, IL-6, TNF-a, IFN-g) by the macrophages. Anti-TNF-a antibody partially suppressed the anti-tumor activity of the culture supernatant of the macrophages incubated with the lipopolysaccharide but not with the gelatin. The gelatin induced anti-tumor activity of the macrophages of C3H/HeJ as well as C3H/HeN mice whereas the lipopolysaccharide did only in C3H/HeN mice. The macrophages stimulated in vitro by the gelatin exerted anti-tumor activity in vivo. Moreover, the gelatin stimulated peritoneal exudates cells in vivo when subcutaneously administered with them. Conclusions: Porcine skin gelatin induces anti-tumor activity of macrophages in mice and its magnitude is greater than that of lipopolysaccharide of E. coli. Its mechanism is different from that of the lipopolysaccharide but not fully clarified. Цель: изучить in vitro противоопухолевую активность мышиных перитонеальных макрофагов, индуцированную желатином кожи свиньи. Методы: противоопухолевую активность макрофагов оценивали по включению меченного тимидина опухолевыми клетками-мишенями. Уровень цитокинов, секретируемых в культуральную среду, определяли с помощью ELISA. Результаты: cпособность желатина индуцировать противоопухолевую активность макрофагов была сильнее, чем у липополисахарида E. coli. Комбинация липополисахарида и интерферона-γ (IFN-γ) синергично стимулировала макрофаги, что показано и для комбинации желатина с IFN-γ. Противоопухолевая активность культурального супернатанта макрофагов, инкубированных с желатином, была выше, чем в случае применения липополисахарида, хотя липополисахарид индуцировал более сильную секрецию противоопухолевых цитокинов (IL-1, IL-6, TNF-α, IFN-γ) макрофагами. Антитела против TNF-α частично угнетали противоопухолевую активность культурального супернатанта макрофагов, инкубированных с липополисахаридом, но не с желатином. Желатин индуцировал противоопухолевую активность макрофагов как C3H/HeJ мышей, так и мышей C3H/ HeN, в то время как липополисахарид влиял только на макрофаги C3H/HeN мышей. Макрофаги, стимулированные in vitro, показывали противоопухолевую активность in vivo. Более того, желатин стимулировал клетки перитонеального экссудата in vivo при одновременном подкожном введении. Выводы: желатин свиной кожи индуцирует противоопухолевую активность макрофагов у мышей, причем более эффективно, чем липополисахарид E. coli. Механизм действия желатина отличается от механизма действия липополисахарида и остается пока невыясненным до конца